2017
DOI: 10.1002/1873-3468.12753
|View full text |Cite
|
Sign up to set email alerts
|

Generating enzyme and radical‐mediated bisubstrates as tools for investigating Gcn5‐related N‐acetyltransferases

Abstract: Gcn5-related N-acetyltransferases (GNATs) are found in all kingdoms of life and catalyze important acyl transfer reactions in diverse cellular processes. While many 3D structures of GNATs have been determined, most do not contain acceptor substrates in their active sites. To expand upon existing crystallographic strategies for improving acceptor-bound GNAT structures, we synthesized peptide substrate analogs and reacted them with CoA in PA4794 protein crystals. We found two separate mechanisms for bisubstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Of the GNATs that have had their kinetic mechanism experimentally determined, these enzymes overwhelmingly favor a direct transfer/sequential mechanism regardless of the identity of their acceptor substrate classification. Indeed, a large number of kinetic studies have shown that Gcn5/pCAF histone N- acetyltransferases (HATs) ( Jiang et al, 2012 ), arylalkylamine N- acetyltransferases (AANATs) ( Dempsey et al, 2014 ; Battistini et al, 2019 ), aminoglycoside N- acetyltransferases (AACs) ( Vetting et al, 2008b ), spermidine/spermine N- acetyltransferases (SSATs) ( Bewley et al, 2006 ; Filippova et al, 2015 ), and GNATs with unknown native substrates ( Majorek et al, 2017 ; Reidl et al, 2017 ) all utilize some form of a direct transfer mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Of the GNATs that have had their kinetic mechanism experimentally determined, these enzymes overwhelmingly favor a direct transfer/sequential mechanism regardless of the identity of their acceptor substrate classification. Indeed, a large number of kinetic studies have shown that Gcn5/pCAF histone N- acetyltransferases (HATs) ( Jiang et al, 2012 ), arylalkylamine N- acetyltransferases (AANATs) ( Dempsey et al, 2014 ; Battistini et al, 2019 ), aminoglycoside N- acetyltransferases (AACs) ( Vetting et al, 2008b ), spermidine/spermine N- acetyltransferases (SSATs) ( Bewley et al, 2006 ; Filippova et al, 2015 ), and GNATs with unknown native substrates ( Majorek et al, 2017 ; Reidl et al, 2017 ) all utilize some form of a direct transfer mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This new insight into the enzymatic mechanism also explains the observed inactivity of monomeric DapE constructs [ 10 ]. This products-bound DapE structure has enabled further refinement of a mechanistic hypothesis for amide bond cleavage by DapE enzymes, supported by our products-bound transition state modeling (PBTSM) approach [ 14 , 15 ], which in turn will facilitate inhibitor identification.…”
Section: Introductionmentioning
confidence: 99%
“…12 The requirement of this His residue explains the observed inactivity of a truncated, monomeric construct of DapE. 6 The product-bound structure, aided by our product-bound transition state modeling (PBTSM) approach, 12,13 enabled further refinement of the proposed reaction mechanism of DapE that will facilitate inhibitor identification 14−16 for the discovery of new antibiotics that inhibit DapE. We report herein a new atomic-resolution (1.3 Å) X-ray crystal structure of NmDapE (PDB entry 5UEJ) with sulfate ions bound in the substrate recognition pocket.…”
mentioning
confidence: 99%